Effectiveness, durability and wear of anti-slip treatments for resilient floor coverings - Derler, S.; Huber, R.; Kausch, F.; Meyer, V.R. (Safety science, 2015)
•Anti-slip treatments and coatings for resilient floor coverings are not durable.•Wear due to pedestrian traffic considerably changes slip resistance within months.•Due to wear, smooth surfaces are roughened while rough surfaces are smoothed.•Floor coverings with high slip resistance are safer than later surface treatments. Adequate slip resistance of floor coverings is a prerequisite for safe walking. The incidence of slips and falls, however, indicates that insufficient slip resistance is a problem frequently arising in practice. Poor slip resistance can be a consequence of inadequate floor material and surface properties, or it can be caused by wear and maintenance. Various treatments and products are commercially available in order to improve or restore the slip resistance of problematic surfaces. In this study, the effectiveness and durability of different categories of anti-slip treatments for resilient floor coverings were investigated in a long-term field test. Repeated measurements of friction coefficients showed that anti-slip coatings initially improved the slip resistance before gradually losing their positive effect, typically with a half-life period of about 3months. Safety coatings as well as slip-resistant adhesive tapes increased the slip resistance effectively and proved to be relatively durable, although being affected by significant mechanical wear. Scanning electron microscopy showed that the predominant wear mechanisms of the investigated floor coverings and anti-slip treatments are roughening of smooth surfaces, smoothing of rough surfaces, and intrusion of hard particles into polymers. The main and probably general result of our study is that all kinds of anti-slip treatments (coatings, tapes) gradually lose their positive effect due to wear during use.